Battery negative plate and battery

By using a three-dimensional conductive network adhesive and silicon-based anode material that cross-links a phenylboric acid compound based on a phenylboric acid compound and a silicon-based anode material in lithium-ion batteries, the performance degradation caused by volume expansion of lithium-ion batteries is solved, and higher cycle stability and reversible capacity are achieved.

CN119833573AActive Publication Date: 2025-04-15SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411838420.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-15
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials in lithium-ion batteries have degraded battery performance due to volume expansion, and insufficient cycle stability and reversible capacity, which limits the further improvement of battery performance.

Method used

A three-dimensional conductive network adhesive obtained by cross-linking of modified polyacrylic compounds based on phenylboric acid compounds and hydroxylated carbon nanotubes is used to combine silicon-based anode materials to form a special three-dimensional conductive network to enhance the mechanical strength and flexibility of the anode.

Benefits of technology

It improves the cycle stability, reversible capacity and electrochemical impedance of lithium-ion batteries, reduces the consumption of electrolyte, and shows excellent rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187355360000051
    Figure BDA0005187355360000051
  • Figure BDA0005187355360000061
    Figure BDA0005187355360000061
  • Figure BDA0005187355360000071
    Figure BDA0005187355360000071
Patent Text Reader

Abstract

The invention provides a battery negative electrode plate and a battery, the battery negative electrode plate comprises a silicon-based negative electrode active material and a binder, the binder is a product obtained by crosslinking a phenylboronic acid compound modified polyacrylic acid compound and a hydroxylated carbon nanotube, the silicon-based negative electrode active material comprises at least one of a silicon material, a silicon oxide material, a silicon carbon material and a silicon alloy material. The invention provides a battery negative plate. A three-dimensional conductive network binder based on crosslinking of a phenylboronic acid compound modified polyacrylic acid compound and a hydroxylated carbon nanotube and a silicon-based negative electrode material are adopted. The network structure provides excellent mechanical strength and flexibility for the negative electrode, and due to the excellent mechanical strength and flexibility, the silicon negative electrode shows excellent cycling stability, high reversible capacity and stable electrochemical impedance in a battery test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a battery negative electrode sheet and a battery. Background Art

[0002] In the current rapid development of energy storage technology, lithium-ion batteries (LIBs) have become the preferred power source for portable electronic devices and electric vehicles due to their high energy density, long cycle life and environmental friendliness. However, with the growing demand for higher energy density and faster charging speed, existing graphite anode materials are gradually approaching their theoretical capacity limit, which limits the further improvement of LIBs performance. Therefore, the development of new high-capacity anode materials has become the key to promoting the development of battery technology.

[0003] Silicon (Si) is an emerging anode material due to its extremely high theoretical specific capacity (about 4200mAh g -1 ), which is an order of magnitude higher than traditional graphite materials, and is widely considered to be a strong candidate material for improving the energy density of lithium-ion batteries. However, silicon anodes undergo significant volume expansion (up to 400%) during charging and discharging. This volume change may lead to the pulverization of active materials, destruction of electrode structures, and continuous consumption of electrolytes, resulting in increased internal resistance of the battery, rapid capacity decay, and decreased cycle stability. These challenges have severely restricted the commercialization of silicon anodes. In order to solve these problems, the electrochemical performance of the above-mentioned batteries can be improved by selecting a suitable binder system. Binders are an important component of lithium battery anode materials. Binders adhere conductive agents and active materials to current collectors, ensure the conductive path of the electrode structure, and thus improve the overall electrochemical performance of the anode. At present, traditional binders, such as polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), and carboxymethyl cellulose (CMC), are insufficient to adapt to the volume expansion of silicon-based materials on the cycle stability, reversible capacity, and electrochemical impedance of the battery due to their poor intermolecular interactions and brittleness. Summary of the invention

[0004] The present invention aims at the above-mentioned problems, makes up for the deficiencies of the prior art, and provides a lithium battery negative electrode sheet and a battery.

[0005] In a first aspect, the present invention provides a battery negative electrode sheet, comprising a silicon-based negative electrode active material and a binder, wherein the binder is a product obtained by cross-linking a polyacrylic acid compound modified by a phenylboronic acid compound and hydroxylated carbon nanotubes, and the silicon-based negative electrode active material comprises at least one of a silicon material, a silicon oxide material, a silicon-carbon material and a silicon alloy material.

[0006] The present invention provides a battery negative electrode sheet, which uses a three-dimensional conductive network binder based on phenylboronic acid modified polyacrylic acid compound and cross-linked hydroxylated carbon nanotubes, and a silicon-based negative electrode material. On the one hand, the phenylboronic acid group of the binder can be in situ cross-linked with the hydroxyl group (-OH) on the surface of the hydroxylated carbon nanotube (OHCNT) to form a borate ester, and on the other hand, the phenylboronic acid can also react with the hydroxyl group on the surface of the negative electrode active material to form a borate ester, and the phenylboronic acid can also self-cross-link to form a cycloboroxane structure, forming a special three-dimensional conductive network. This network structure provides excellent mechanical strength and flexibility for the negative electrode. The silicon negative electrode shows excellent cycle stability, high reversible capacity and stable electrochemical impedance in battery testing; the phenylboronic acid group in the binder can form a more stable electrolyte interface (SEI) film, increasing the lithium ion (Li + ) migration rate, thereby reducing the consumption of electrolyte and showing excellent rate performance.

[0007] Specifically, in some embodiments of the present invention, the mass ratio of the phenylboric acid compound to the polyacrylic acid compound is 0.19-1.33; more specifically, the mass ratio of the phenylboric acid compound to the polyacrylic acid compound is 0.19, 0.38, 0.57, 0.76, 0.95, 1.14, 1.33; preferably, the mass ratio of the phenylboric acid compound to the polyacrylic acid compound is 0.57-0.95.

[0008] Specifically, in some embodiments of the present invention, the mass ratio of the polyacrylic acid compound modified by the phenylboric acid compound to the hydroxylated carbon nanotubes is 1.0-6.0. More specifically, the mass ratio of the polyacrylic acid compound modified by the phenylboric acid compound to the hydroxylated carbon nanotubes is 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0; preferably, the mass ratio of the polyacrylic acid compound modified by the phenylboric acid compound to the hydroxylated carbon nanotubes is 2.0-3.0.

[0009] In the present invention, a too large mass ratio of the phenylboronic acid modified polyacrylic acid compound to the hydroxylated carbon nanotubes will result in an excessively large crosslinking density, making the polymer network complicated, resulting in an excessively high slurry viscosity and inability to disperse evenly. A too small mass ratio will result in the polymer being unable to adapt to the expansion of the silicon negative electrode volume, resulting in poor cycle performance of the battery.

[0010] Specifically, in some embodiments of the present invention, the phenylboronic acid compound is at least one of 3-aminophenylboronic acid, 2-aminophenylboronic acid, 4-aminophenylboronic acid, [3-(2-aminoethyl)phenyl]boric acid, and 3-aminomethylphenylboronic acid.

[0011] Specifically, in some embodiments of the present invention, the polyacrylic acid compound includes at least one of polyacrylic acid, polymethacrylic acid, sodium polyacrylate, lithium polyacrylate, sodium polymethacrylate, and lithium polymethacrylate.

[0012] Specifically, in some embodiments of the present invention, the polyacrylic acid compound modified by the phenylboronic acid compound is cross-linked with the hydroxylated carbon nanotubes, comprising:

[0013] S1. Dissolve a polyacrylic acid compound and a base in water, add an aqueous solution of a phenylboric acid compound to obtain a mixed solution, cool the mixed solution to 2°C-7°C, add an activator, and react for 10-14 hours to obtain a polyacrylic acid compound modified with a phenylboric acid compound;

[0014] S2: adding hydroxylated carbon nanotubes and dispersant into water and ultrasonicating for 1-3 hours to obtain a dispersion, and mixing it with the polyacrylic acid compound modified by the phenylboronic acid compound to obtain a binder.

[0015] Compared with the traditional binder preparation process, the binder preparation process of the present invention adopts an aqueous solvent, thereby simplifying the synthesis process and improving the preparation efficiency. The component formula combining the binder and the conductive agent into one shows the potential for direct industrial application.

[0016] Specifically, in some embodiments of the present invention, the silicon material is nano-silicon or micro-silicon material;

[0017] The silicon oxide material is SiO x Materials, where 0≤x≤2;

[0018] The silicon-carbon material is a silicon-based material containing silicon and carbon material and / or containing SiO y and a silicon-based material of a carbon material, wherein 0≤y≤2.

[0019] Specifically, in some embodiments of the present invention, the mass ratio of the silicon-based negative electrode active material to the binder is 85:15-97:3. More specifically, the mass ratio of the silicon-based negative electrode active material to the binder is 85:15, 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, 97:3. Preferably, the mass ratio of the silicon-based negative electrode active material to the binder is 92:8-95:5.

[0020] Specifically, in some embodiments of the present invention, the base is at least one of lithium hydroxide, sodium hydroxide, and potassium hydroxide.

[0021] Specifically, in some embodiments of the present invention, the activator is at least one of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, dicyclohexylcarbodiimide, and N,N'-diisopropylcarbodiimide.

[0022] In a second aspect, the present invention also provides a method for preparing a negative electrode sheet of a battery, comprising the following steps: using a mixer to evenly mix the negative electrode active material and the binder to obtain a negative electrode slurry, using a coating machine to coat the negative electrode slurry on the surface of the current collector, and obtaining the negative electrode sheet of the battery after drying and cutting, wherein the active material loading is about 2.0-5.0 mg·cm -2 .

[0023] The present invention also provides a battery, comprising the above-mentioned battery negative electrode sheet, wherein the battery is a lithium ion battery, a semi-solid battery or a solid-state battery.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention provides a battery negative electrode sheet, which uses a silicon-based negative electrode active material, and adopts a binder based on a cross-linked polyacrylic acid compound modified by a phenylboronic acid compound and a hydroxylated carbon nanotube, and a silicon-based negative electrode material. On the one hand, the phenylboronic acid group of the binder can be in situ cross-linked with the hydroxyl group (-OH) on the surface of the hydroxylated carbon nanotube (OHCNT) to form a borate ester, and on the other hand, the phenylboronic acid can also react with the hydroxyl group on the surface of the negative electrode active material to form a borate ester, and the phenylboronic acid can also self-cross-link to form a cycloboroxane structure, forming a special three-dimensional conductive network, which provides excellent mechanical strength and flexibility for the negative electrode. The silicon negative electrode shows excellent cycle stability, high reversible capacity and stable electrochemical impedance in battery testing; the phenylboronic acid group in the binder can form a more stable electrolyte interface film (SEI), increase the lithium ion (Li + ) migration rate, thereby reducing the consumption of electrolyte and showing excellent rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The schematic diagram of the synthesis of the modified polyacrylic acid compound modified by 3-aminophenylboronic acid in Example 1;

[0027] Figure 2 This is a schematic diagram of the binder synthesis principle in Example 1;

[0028] Figure 3 This is the infrared detection spectrum of the polyacrylic acid compound modified by phenylboronic acid compound;

[0029] Figure 4 This is the infrared detection spectrum of the binder. DETAILED DESCRIPTION

[0030] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0031] Example 1

[0032] This embodiment provides a negative electrode plate for a battery, comprising a nano-silicon active material and a binder, wherein the binder is a product obtained by cross-linking a polyacrylic acid compound modified by a phenylboronic acid compound and a hydroxylated carbon nanotube.

[0033] Preparation of binder:

[0034] S1 Take 1g polyacrylic acid (PAA) and 0.05g LiOH and dissolve them in 20g water, add 0.76g 3-aminophenylboronic acid (APBA) to obtain a mixed solution, cool the mixed solution to 4°C and add 1.06g 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and keep it at 4°C for 12 hours. Purify it by dialysis to obtain 3-aminophenylboronic acid modified polyacrylic acid. The synthesis principle is as follows Figure 1 shown.

[0035] S2: 0.3 g of hydroxylated carbon nanotubes (OHCNT) and 0.33 g of dispersant were added to 15.75 g of water and ultrasonicated for 2 hours to obtain a hydroxylated carbon nanotube dispersion. 0.75 g of 3-aminophenylboronic acid-modified polyacrylic acid was mixed with the hydroxylated carbon nanotube dispersion, and the mass ratio of 3-aminophenylboronic acid-modified polyacrylic acid to hydroxylated carbon nanotubes (OHCNT) was 5:2 to obtain a binder (PBO). The synthesis principle is as follows: Figure 2 shown.

[0036] Preparation of negative electrode sheet: According to the weight ratio, nano-silicon active material and binder were mixed and stirred in a blender at a mass ratio of 93:7 to obtain negative electrode slurry with suitable viscosity. The slurry was coated on the copper current collector using a coating machine. After vacuum drying at 120°C for 12 hours, the negative electrode was cut into discs with a diameter of 12 mm. The active material loading was about 3.0 mg cm -2 .

[0037] Half-cell preparation: The electrochemical performance was evaluated by using CR2025 type half-cells assembled by sandwiching a separator (about 25 μm) between the above binder based working electrode and lithium foil counter electrode.

[0038] Full battery preparation: using LiNi 0.8 Co 0.1 Mn0.1 The O2 (NCM811) positive electrode and the above negative electrode were assembled to obtain a full battery, and the loading capacity of NCM811 was 3.5 mAh cm -2 .

[0039] In this embodiment, the infrared detection results of polyacrylic acid modified with 3-aminophenylboronic acid are as follows: Figure 3 As shown, at 2877cm -1 The absorption peak at 1465 cm represents the stretching vibration of the CH bond of the benzene ring. -1 The absorption peak at 1350cm is the in-plane deformation vibration of the NH bond. -1 The absorption peak represents the stretching vibration of the BO bond, proving that 3-aminophenylboronic acid successfully modified polyacrylic acid.

[0040] The infrared detection results of the adhesive are as follows: Figure 4 As shown, the binder is at 1231cm -1 The absorption peak represents the stretching vibration of BOC, 735cm -1 The absorption peak represents the stretching vibration of BOB, proving the successful combination of 3-aminophenylboronic acid modified polyacrylic acid and OH-CNT.

[0041] Example 2-27

[0042] This example is used to compare and illustrate the lithium-ion battery disclosed in the present invention, and includes most of the operating steps in the above-mentioned Example 1, and the difference lies in: the synthesis conditions of the negative electrode active material, the polyacrylic acid compound modified by the phenylboronic acid compound and the binder, the synthesis components of the polyacrylic acid compound modified by the phenylboronic acid compound and the binder, and their masses and mass ratios are shown in Table 1.

[0043] Comparative Example 1

[0044] Compared with Example 1, the binder used in this comparative example directly mixes polyacrylic acid with hydroxylated carbon nanotubes, and the rest is consistent with Example 1.

[0045] Table 1

[0046]

[0047]

[0048] The performance test method for the lithium ion batteries of Examples 1-27 and Comparative Example 1 is as follows: Half-cell performance test

[0049] Experiment 1

[0050] Cyclic performance test: At 25°C, discharge at 0.2C rate to a voltage of 0.01V, then charge at 0.2C rate to 2V, this is a charge and discharge cycle, repeat this charge and discharge cycle 400 times. Capacity retention rate after 400 cycles = discharge capacity after 400th cycle / discharge capacity after the first cycle × 100%, the test results are shown in Table 2.

[0051] Experiment 2

[0052] Rate performance test: At 25°C, the battery was charged to a charging capacity of 2V at constant currents of 0.2C, 0.5C, 1C, and 2C respectively. The test results are shown in Table 2.

[0053] Full battery performance test experiment

[0054] Experiment 3

[0055] Cyclic performance test: The full battery was first tested at 0.05C (1C = 200 mAh g- 1 ) for 2 cycles, then activated at 0.1C for 2 cycles, and the capacity retention rate after cycling 200 times at a current density of 2.5V to 4.25V and 0.5C. The test results are shown in Table 2.

[0056] Experiment 4

[0057] Electrochemical impedance spectroscopy: Connect to the EIS electrochemical workstation and set the frequency to 10 -2 -10 -6 Hz, amplitude 5mVRMS; EIS impedance of the full battery after 2 cycles and EIS impedance after 100 cycles, the test results are shown in Table 2.

[0058] Table 2

[0059]

[0060]

[0061] It can be seen from the data in Table 2 that: from the battery test performance of Examples 1-27 and Comparative Example 1, it can be seen that the battery prepared by the binder based on the cross-linking of the polyacrylic acid compound modified by the phenylboronic acid compound and the hydroxylated carbon nanotube and the silicon-based negative electrode material of the present invention is superior to the battery prepared by using the polyacrylic acid as the binder in Comparative Example 1 in terms of cycle stability, charging capacitance and electrochemical impedance stability, indicating that the phenylboronic acid group of the binder of the present invention can be in situ cross-linked with the hydroxyl group (-OH) on the surface of the hydroxylated carbon nanotube (OHCNT) to form a boric acid ester, and on the other hand, phenylboric acid can also react with the hydroxyl group on the surface of the negative electrode active material to form a boric acid ester, and phenylboric acid can also self-cross-link to form a cycloboroxine structure, forming a special three-dimensional conductive network. This network structure provides the negative electrode with excellent mechanical strength and flexibility, and the silicon negative electrode exhibits excellent cycle stability, high reversible capacity and stable electrochemical impedance in battery tests; from the battery performance test results of Examples 1-5 and Examples 6-7, it can be seen that when the mass ratio of phenylboronic acid compounds / polyacrylic acid compounds is in the range of 0.19-1.33, the battery's cycle stability, charging capacitance and electrochemical impedance stability are better; from the battery performance test results of Examples 1, Examples 8-10 and Examples 11-12, it can be seen that when the mass ratio of phenylboronic acid compounds modified polyacrylic acid compounds and hydroxylated carbon nanotubes is in the range of 1.0-6.0, the battery's cycle stability, charging capacitance and electrochemical impedance stability are better.

[0062] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A battery negative electrode sheet, characterized in that: The invention comprises a silicon-based negative electrode active material and a binder. The binder is a product obtained by cross-linking a polyacrylic acid compound modified by a phenylboronic acid compound and hydroxylated carbon nanotubes. The silicon-based negative electrode active material comprises at least one of a silicon material, a silicon oxide material, a silicon-carbon material and a silicon alloy material.

2. A battery negative electrode sheet according to claim 1, characterized in that: The mass ratio of the phenylboric acid compound to the polyacrylic acid compound is 0.19-1.

33.

3. A battery negative electrode sheet according to claim 1, characterized in that: The mass ratio of the phenylboronic acid compound modified polyacrylic acid compound to the hydroxylated carbon nanotube is 1.0-6.

0.

4. A battery negative electrode sheet according to claim 1, characterized in that: The phenylboronic acid compound is at least one of 3-aminophenylboronic acid, 2-aminophenylboronic acid, 4-aminophenylboronic acid, [3-(2-aminoethyl)phenyl]boric acid and 3-aminomethylphenylboronic acid.

5. A battery negative electrode sheet according to claim 1, characterized in that: The polyacrylic acid compound includes at least one of polyacrylic acid, polymethacrylic acid, sodium polyacrylate, lithium polyacrylate, sodium polymethacrylate, and lithium polymethacrylate.

6. A battery negative electrode sheet according to any one of claims 1 to 5, characterized in that: The polyacrylic acid compound is modified by phenylboronic acid compound and cross-linked with hydroxylated carbon nanotubes, including: S1. Dissolve a polyacrylic acid compound and a base in water, add an aqueous solution of a phenylboric acid compound to obtain a mixed solution, cool the mixed solution to 2°C-7°C, add an activator, and react for 10-14 hours to obtain a polyacrylic acid compound modified with a phenylboric acid compound; S2: adding hydroxylated carbon nanotubes and dispersant into water and ultrasonicating for 1-3 hours to obtain a dispersion, and mixing it with the polyacrylic acid compound modified by the phenylboronic acid compound to obtain a binder.

7. A battery negative electrode sheet according to claim 1, characterized in that: The silicon material is nano-silicon or micro-silicon material; The silicon oxide material is SiO x Materials, where 0≤x≤2; The silicon-carbon material is a silicon-based material containing silicon and carbon material and / or containing SiO y and a silicon-based material of a carbon material, wherein 0≤y≤2.

8. A battery negative electrode sheet according to claim 1, characterized in that: The mass ratio of the silicon-based negative electrode active material to the binder is 85:15-97:

3.

9. A battery, characterized in that: The battery negative electrode sheet comprises any one of claims 1 to 8, wherein the battery is a lithium ion battery, a semi-solid battery or a solid-state battery.

Citation Information

Patent Citations

  • Multifunctional self-repairing adhesive for lithium-sulfur battery positive electrode, preparation method and application thereof

    CN112652773A

  • Negative plate and battery

    CN118867134A

  • Binders for silicon electrodes in lithium-ion batteries

    US20210257620A1

Cited By

  • Silicon-carbon negative electrode material, preparation method thereof and lithium ion battery

    CN121260759A